Pulsatile Vascular Afterload Measurement Improves Prediction of Right‐Sided Heart Dysfunction in Undifferentiated and Left‐Sided Pulmonary Hypertension - Sara Louise Hungerford; Katherine Kearney; Christina Li; Ning Song; Kay Everett; Gaurav Gulati; Nicholas Olsen; Edmund Lau; Andrew Jabbour; Nicole Bart; Eugene Kotlyar; David Muller; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The association between raised pulmonary artery pressures, pulmonary vascular resistance (PVR), and right‐sided heart dysfunction is well recognized. The added value of pulsatile indices, specifically pulmonary arterial compliance (PAC) and characteristic impedance, remains unclear. This study aimed to identify the optimal vascular afterload model for predicting right‐sided heart dysfunction in newly diagnosed pulmonary hypertension (PH). METHODS AND RESULTS This was a prospective cohort study of 86 patients with suspected PH (60±16 years; 66 women) who underwent right‐sided heart catheterization and cardiac magnetic resonance imaging. Right ventricular end‐diastolic volume index (RVEDVi) and right atrial (RA) volume index were measured using cardiac magnetic resonance imaging. Vascular resistance, PAC, and characteristic impedance were measured using pulmonary artery pressure from right‐sided heart catheterization and pulmonary artery flow from cardiac magnetic resonance imaging. Optimal model fit was determined by the lowest Akaike Information Criterion value. A total of 58% of patients had a right ventricular ejection fraction <50%, 63% had an increased RVEDVi, and 56% had an increased RA volume index. Overall, PVR was the best predictor of right ventricular ejection fraction <50% (P<0.01), increased RVEDVi (P<0.01), and RA volume index (P=0.02). However, for patients with a PVR <240 dynes.s.cm−5, PACclinical outperformed PVR in predicting right ventricular ejection fraction <50% (P=0.02) and increased RVEDVi (P=0.05). A 3‐component model (PVR, PACclinical, and characteristic impedance) best predicted RA dilatation (P=0.05). In paired analysis, alternative methods of PAC quantification better predicted increased RVEDVi (PACdecay P=0.02) and RA volume index (PACarea P=0.02). PACclinical <2.3 mL/mm Hg optimally predicted right‐sided heart dysfunction (area under the curve, 0.768) and increased the AUC for PVR in undifferentiated/left‐sided PH (0.89 versus 0.72). Conclusions Pulsatile vascular afterload measurement improves right‐sided heart dysfunction prediction in undifferentiated/left‐sided PH. More accurate PAC measurement methods could further enhance prognostic accuracy, while a PVR ≥240 dynes.s.cm−5 remains a valuable threshold for precapillary PH.